2019
DOI: 10.1021/acs.macromol.9b00952
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Versatility of Silane/Iodonium Salt as Redox Free Radical, Cationic, and Photopolymerization Initiators

Abstract: The use of safe, economic, and efficient initiators in redox free radical polymerization (RFRP) at room temperature (RT) or in cationic polymerization (CP) and as photoinitiators (PI) for both free radical polymerization (FRP) and CP as well as their use for the manufacture of composites are investigated. Remarkably, initiators based on silane/iodonium salt couples are proposed here for their versatility for all the different polymerization modes which is a quite unique feature. The reactions are followed by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Wang et al [ 57 ] reported a novel combination of a photoinitiator based on diaryliodonium salt and silanes that gave adjustable gel time of polymerization as well as excellent storage stability for bisepoxides. This unique formulation provided the advantage of multi-mechanism curing, which includes redox free radical, free radical and thermal/UV-induced cationic polymerization.…”
Section: Onium Salt Photoinitiators For Different Epoxy Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 57 ] reported a novel combination of a photoinitiator based on diaryliodonium salt and silanes that gave adjustable gel time of polymerization as well as excellent storage stability for bisepoxides. This unique formulation provided the advantage of multi-mechanism curing, which includes redox free radical, free radical and thermal/UV-induced cationic polymerization.…”
Section: Onium Salt Photoinitiators For Different Epoxy Monomersmentioning
confidence: 99%
“…This unique formulation provided the advantage of multi-mechanism curing, which includes redox free radical, free radical and thermal/UV-induced cationic polymerization. They proved the positive influence of silane groups in cationic photo polymerization of epoxy, where Si-H groups where able to participate in the initiation and promotion of epoxy polymerization [ 57 ].…”
Section: Onium Salt Photoinitiators For Different Epoxy Monomersmentioning
confidence: 99%
“…The strippable films were synthesized by visible light polymerization, as illustrated in Scheme 1 . Upon exposure to visible light, CQ is converted to an excited state before forming free radicals (CQ−H•) by abstracting a hydrogen atom from EDB [ 35 ]. TBA and side chains of 1,2-addition LPB are triggered by CQ−H• free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Photopolymerization is a facile approach to manufacturing of polymer materials. [1][2][3] There has been a trend of replacing ultraviolet (UV) with visible and near-infrared light. [4][5][6] Longer wavelengths have greater depth of penetration into both biological and synthetic materials, making them particularly attractive for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Photopolymerization is a facile approach to manufacturing of polymer materials 1–3 . There has been a trend of replacing ultraviolet (UV) with visible and near‐infrared light 4–6 .…”
Section: Introductionmentioning
confidence: 99%